ANALYTIC APPROACH FOR LOVE WAVE DISPERSION IN AN INHOMOGENEOUS LAYER LYING OVER AN IRREGULAR POROUS HALF-SPACE - Gupta, S; Pramanik, S; Smita; Pramanik, A (TWMS journal of applied and engineering mathematics, 2019)
The present work examines the possibility of Love wave dispersion in an irregular interface of two different media expressively as an inhomogeneous layer and porous half-space. Dispersion equation has been computed in a compact form following the expansion of transformation method, perturbation technique, Whittaker equation and its derivative. The dispersion equation coincides with the classical equation of Love type wave which agrees with the pre-established results. The graphs are sketched to show the effect of porosity, irregularity and inhomogeneous parameters. Keywords: Love wave, Irregularity, Porous, Perturbation technique, Dispersion equation. AMS Subject Classification: 74A05, 74A10, 74B05, 74B20.